The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/mbo3.1287
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal phytoplankton and geochemical shifts in the subsurface chlorophyll maximum layer of a dimictic ferruginous lake

Abstract: Subsurface chlorophyll maxima layers (SCML) are ubiquitous features of stratified aquatic systems. Availability of the micronutrient iron is known to influence marine SCML, but iron has not been explored in detail as a factor in the development of freshwater SCML. This study investigates the relationship between dissolved iron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…This study also found that cryptophyte abundance had a strong positive correlation to Secchi depth, which indicates that cryptophytes are oftentimes found and therefore more adapted to low light conditions. This low light adaptation could be resultant by an abundance of chlorophyll within these cryptophytes (Swanner et al, 2022).…”
Section: Phytoplankton Communities and Physicochemical Gradients With...mentioning
confidence: 99%
“…This study also found that cryptophyte abundance had a strong positive correlation to Secchi depth, which indicates that cryptophytes are oftentimes found and therefore more adapted to low light conditions. This low light adaptation could be resultant by an abundance of chlorophyll within these cryptophytes (Swanner et al, 2022).…”
Section: Phytoplankton Communities and Physicochemical Gradients With...mentioning
confidence: 99%